The Power Reduction Policy and Its Impact on Cellular Network Performance under GSM-R Interference: A Case Study of KCJB-Indosat - Luthia Defit Degita; Dadang Gunawan (Journal Research of Social Science, Economics, and Management, 2025)
This research aims to evaluate the impact of transmitter power reduction policies implemented to mitigate spectrum interference between the GSM-R system and cellular networks on the Jakarta–Bandung High-Speed Railway (KCJB), with a specific focus on Indosat. Employing a quantitative descriptive method complemented by strategic management analysis (SWOT, IFE–EFE, QSPM), this study analyzes technical parameters (RSRP, traffic volume, active users) and business indicators (daily revenue, customer churn rate). Findings indicate significant service quality degradation, marked by a 35.7% decrease in RSRP coverage, 34% reduction in daily traffic volume, and 33% decrease in active users. Additionally, business performance suffered, reflected by 5.8% drop in daily revenue and a substantial rise in customer churn. Strategic analysis suggests joint spectrum management and installation of band-pass filters on the GSM-R side as the optimal mitigation strategy. This study underscores the necessity of coordinated technical and regulatory solutions to balance interference mitigation with telecommunication service sustainability.